Information Sharing and Information Acquisition: Ownership and Coverage - Artashes Karapetyan; Bogdan Stacescu (Norges Bank, 2011)
We examine the conditions required for the existence of private credit bureaus, their ownership and coverage. Our model implies that bank consortia will most likely be preferred by banks, but that they will lead to restricted coverage. Independent credit bureaus have higher coverage, but they require good institutions. This implies an important role for public credit registers in developing countries with weak institutions. Our empirical findings largely support the implications of our model.
hdl:11250/2496936
Keywords: G20; D82; L12; 330; information sharing; credit markets; default; adverse selection